Muslim Minorities in Western Societies: The Medieval Scene - ’Abd Al-Rahim, Muddathir (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Muslim Minorities in Western Societies: The Medieval Scene